2010
DOI: 10.1088/0022-3727/43/34/345103
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of InAs0.926Sb0.063N0.011/InAs multi-quantum wells in the mid-infrared spectral range

Abstract: We report on the epitaxial growth and photoluminescence of InAs 0.926 Sb 0.063 N 0.011 /InAs multi-quantum wells grown using plasma-assisted molecular beam epitaxy. These dilute nitride quantum wells exhibit bright photoluminescence in the midinfrared spectral range up to a temperature of 250 K without any post-growth annealing. Consideration of the power dependent photoluminescence behaviour are consistent with a type I band line-up in these quantum wells, arising from a strong lowering of the conduction band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…We can also notice weak fluctuations on both sides of the InAs peak in sample (A), which probably originate from the QD layers. In a similar manner to multiple quantum wells [25], the multiple QD layers in our samples would be expected to give periodic peaks on both sides of the InAs peak, as the XRD spectrum of sample (D) shows. However, due to the changing thickness of InAs spacer layers between the InSb QD layers, such periodic features cannot be clearly observed from sample (A), and are absent from samples (B) and (C).…”
Section: X-ray Diffractionmentioning
confidence: 82%
“…We can also notice weak fluctuations on both sides of the InAs peak in sample (A), which probably originate from the QD layers. In a similar manner to multiple quantum wells [25], the multiple QD layers in our samples would be expected to give periodic peaks on both sides of the InAs peak, as the XRD spectrum of sample (D) shows. However, due to the changing thickness of InAs spacer layers between the InSb QD layers, such periodic features cannot be clearly observed from sample (A), and are absent from samples (B) and (C).…”
Section: X-ray Diffractionmentioning
confidence: 82%
“…Simulation of the XRD curve gives the Sb and N contents in the well as 5.0% and 0.8%, respectively, so that the strain in the QW is approximately 0.2%. The band structure at 4 K for the QW is shown in Figure 1(b) using the same calculation procedure as described previously [9]. Three heavy hole and one light hole states are confined.…”
Section: Sample Growth and Fabricationmentioning
confidence: 99%
“…To date there have been no reports of LEDs based on dilute nitride material in the mid-infrared spectral range (λ > 3 μm) due to the difficulty in growing epitaxial material of sufficient quality. Our previous work has concentrated on the development and optimisation of the growth of InAsSbN and from which photoluminescence (PL) was obtained up to 250 K from InAsSbN/InAs MQWs [8,9]. It was found that the surfactant effect of Sb enhances the crystalline quality and PL intensity.…”
Section: Introductionmentioning
confidence: 99%
“…III-V semiconductors with small amount of nitrogen (socalled dilute nitrides) such as GaNAs, GaInNAs, GaN-AsSb, or InNAs are under great interest of scientists since last decade due to their unusual physical properties [1][2][3] and potential applications in near [1,[4][5][6][7][8][9][10] and midinfrared [11][12][13][14][15] emitters, solar cells [16][17][18][19][20], and saturable absorber mirrors [21][22][23][24][25]. The most interesting feature of dilute nitrides is that the incorporation of small amount of nitrogen into III-V host causes a significant narrowing of the energy gap with the simultaneous reduction in the lattice constant [1].…”
Section: Introductionmentioning
confidence: 99%